2013
DOI: 10.1589/jpts.25.785
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pelvic Adjustment on the Posture of Female University Students

Abstract: [Purpose] The purpose of this study was to examine the effects of pelvic adjustment via the Gonstead Technique on the posture of female university students. [Subjects] The subjects of this study were 30 female university students who were equally and randomly allocated to a pelvic adjustment group, an experimental group, and a stretching group, a control group. [Methods] Using BackMapper, their trunk inclination (TIN), trunk imbalance (TIM), pelvic position (PPO), pelvic torsion (PTO), pelvic rotation (PRO), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Correct posture is very important because it can affect not only the efficiency of bodily functions but also posture and outer appearance 14 ) . Therefore, this study aimed to determine the effect of running in place on postural correction for normal adults.…”
Section: Discussionmentioning
confidence: 99%
“…Correct posture is very important because it can affect not only the efficiency of bodily functions but also posture and outer appearance 14 ) . Therefore, this study aimed to determine the effect of running in place on postural correction for normal adults.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Park et al (2012) reported that the balance of 20 elderly males was improved through pelvic adjustment using Gonstead techniques9 ) , while Cho (2013) stated that pelvic adjustment improved posture in female university students10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The subjects then resumed the initial posture, rested for 5 seconds, and repeated the stretching one more time. Stretching was done three times per posture for a total of 15 minutes 4 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, FLLI might be improved by pelvic adjustment. High-velocity and low-amplitude (HVLA) adjustment has been widely utilized as a general chiropractic adjustment method 4 ) . Many studies have indicated that leg length inequality (LLI) causes posture alteration 3 ) , limiting exercise and causing tension of the muscles and other soft tissues 5 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation